BIOMASS YIELD AND NUTRITIONAL COMPOSITION IN NATURAL PASTURES IN NORTH-EASTERN AGRO-CLIMATIC ZONE OF TAMIL NADU - Haripriya Chapa; S. Meenakshi Sundaram; R. Venkataramanan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to evaluate the biomass yield and proximate composition of biomass from the natural pastures of Madras Red sheep. Eight villages were selected from the habitat of Madras Red sheep and 40 samples each during rainy and summer season were collected to assess the biomass yield and proximate composition. The study showed that biomass yield and proximate composition were higher during the rainy season during which these sheep completed their breeding, reproduction and lactation. The total dry matter content was higher during the summer season which was able to meet maintenance requirement of sheep during these months. Farmers managed these animals without any supplementary feeding, but during summer the animals were let in the harvested fields where they had access to crop residues for grazing.